Efficiency of Galvanic Effluent Treatment in the city of Rio Verde-Goiás. - Oliveira, Marcos Fernandes de; Couto, Bruno de Oliveira Costa; Aguiar, Ana Carolina Ribeiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
The anthropic impacts on the environment, its perception and prevention are constant objects of studies aimed at improving the quality of life. Within this comprehensive area, the process of galvanization for metals and its generated waste was evaluated here, because galvanization is an effective alternative in the protection against corrosion, and is also a good ally in the useful life of metal parts and although practical and profitable, this process generates a huge volume of slag. This work was intended to verify by atomic absorption spectrophotometry (AAS) the efficiency of the treatment performed in an electroplating plant installed in the city of Rio Verde-Goiás. The acid effluents, with emphasis on hexavalent chromium used in the passivation of the parts, were treated with sodium metabisulfite, keeping the final effluent within a passive threshold for disposal, although it requires post-treatment of liquid waste to maintain environmental safety.